Distribution and Functional Expression of Kv4 Family α Subunits and Associated KChIP β Subunits in the Bed Nucleus of the Stria Terminalis - Rainnie, Donald G. (2014)
Regulation of BNST(ALG) neuronal firing activity is tightly regulated by the opposing actions of the fast outward potassium current, I(A), mediated by α subunits of the Kv4 family of ion channels, and the transient inward calcium current, I(T). Together, these channels play a critical role in regulating the latency to action potential onset, duration, and frequency, as well as dendritic back-propagation and synaptic plasticity. Previously we have shown that Type I–III BNST(ALG) neurons express mRNA transcripts for each of the Kv4 α subunits. However, the biophysical properties of native I(A) channels are critically dependent on the formation of macromolecular complexes of Kv4 channels with a family of chaperone proteins, the potassium channel-interacting proteins (KChIP1–4). Here we used a multidisciplinary approach to investigate the expression and function of Kv4 channels and KChIPs in neurons of the rat BNST(ALG). Using immunofluorescence we demonstrated the pattern of localization of Kv4.2, Kv4.3, and KChIP1–4 proteins in the BNST(ALG). Moreover, our single-cell reverse-transcription polymerase chain reaction (scRT-PCR) studies revealed that mRNA transcripts for Kv4.2, Kv4.3, and all four KChIPs were differentially expressed in Type I–III BNST(ALG) neurons. Furthermore, immunoelectron microscopy revealed that Kv4.2 and Kv4.3 channels were primarily localized to the dendrites and spines of BNST(ALG) neurons, and are thus ideally situated to modulate synaptic transmission. Consistent with this observation, in vitro patch clamp recordings showed that reducing postsynaptic I(A) in these neurons lowered the threshold for long-term potentiation (LTP) induction. These results are discussed in relation to potential modulation of I(A) channels by chronic stress.